Robust consumption decisions under ambiguity for regime switching mean returns - Hening Liu (The University of Manchester, Manchester Business School, 2009)
This paper examines a continuous-time intertemporal consumption and portfolio choice problem for an investor with Du e and Epstein (1992a)'s recursive preferences who worries about model misspecification (model uncertainty) and wants to seek robust decision rules. The expected excess return of a risky asset follows a mean-reverting process. I find that whether the concern about model uncertainty decreases the total demand for equities largely depends on risk aversion and the attitude toward intertemporal substitution. When the elasticity of intertemporal substitution (EIS) is about one and risk aversion is moderate, the concern about model uncertainty increases the proportion of wealth invested in equities. The aversion to model uncertainty also increases the importance of the intertemporal hedging demand in portfolio decisions. The calibration analysis based on the detection-error probabilities shows that the quantitative effect of robustness is almost negligible for both the long sample of Campbell and Viceira (1999) and the short sample of Barberis (2000).
Keywords: 330; robustness; mean-reverting; portfolio choice; Entscheidung bei Unsicherheit; Zeitpräferenz; Portfolio-Management; Mathematische Optimierung; Theorie